Pilu: An underutilized nutritious fruit of arid region - Prakash; Arya, Dhaneshvari (Indian Horticulture, 2025)
Pilu, commonly known as, Jhal, Badapilu, Miswak, or the toothbrush tree, belongs to the Salvadoraceae family. It is an underutilized fruit with significant potential, especially wasteland regions like western Rajasthan and Gujarat. Even with its limited genetic diversity and lack of awareness for production, the tree has excellent chemical properties that makes it valuable in the pharmaceutical industry. The chemical compounds contribute to its impressive pharmacological profile, which includes anti-inflammatory, analgesic, anti-ulcer, anthelmintic, antibacterial, antifungal and diuretic effects. This article highlights the importance of Pilu, focusing on its phytochemical composition and the diverse pharmacological benefits it offers.